How do you solve for (X) in this quadratic equation, 3X^2/(X^2-1)=4/(X-1)


Notice: Undefined variable: position6 in /home/domains2/public_html/painphr.com/show.php on line 143

Guide :

How do you solve for (X) in this quadratic equation, 3X^2/(X^2-1)=4/(X-1)

solve by the use of factorization

Research, Knowledge and Information :



Notice: Undefined variable: go_page in /home/domains2/public_html/painphr.com/show.php on line 211

Quadratic Equation Solver - Math is Fun


Quadratic Equation Solver. If you have an equation of the form "ax 2 + bx + c = 0", we can solve it for you. ... x 2 = 3x -1: x 2 - 3x + 1 = 0: a=1, ...
Read More At : www.mathsisfun.com...

3 Ways to Solve Quadratic Equations - wikiHow


How to Solve Quadratic Equations. A quadratic equation is a polynomial equation in a single variable where the highest exponent of the variable is 2. There are three ...
Read More At : www.wikihow.com...

How do I solve [math]4^x-2^x-2=0[/math] - Quora - A place to ...


... \Leftrightarrow y^2-y-2=0[/math] … omitting quadratic equation resolution ... How do I solve [math]x^6-x^5+3x^4-x^2-3=0 ... How do you solve the problem 4^x = 1/2?
Read More At : www.quora.com...

How do you solve x^2+3x+2=0? | Socratic


x=-2 or x=-1 Two standard ways to solve a quadratic equation: Firstly you could factorise it to the form:- x^2+3x+2=0 x^2+(a+b) ... How do you solve #3x^2 = 108#?
Read More At : socratic.org...

How do you solve x^2 + 3x + 6 = 0 by quadratic formula ...


SOCRATIC Subjects . Science Anatomy ... How do you solve #x^2 + 3x + 6 = 0# by quadratic formula? ... #x^2 +3x +6 =0# The equation is of the form #color ...
Read More At : socratic.org...

How can the quadratic equation [math]x^2 - 3x - 10 = 0[/math ...


How can the quadratic equation [math]x^2 - 3x - 10 = 0[/math] be solved? Update Cancel. Answer Wiki. ... How do you solve 3x^2-2x-3=0 with the quadratic formula?
Read More At : www.quora.com...

Algebra 2 - Solve by using the quadratic formula when c=0, 3x ...


Feb 26, 2013 · http://www.freemathvideos.com in this video tutorial I show you how to solve a quadratic equation by using the quadratic equation. When factoring or ...

Solve The Quadratic Equation X^2- 3x- 2 = 0


Here you find answers to questions like: Solve The Quadratic Equation X^2- 3x- 2 = 0 . Or how to solve the quadratic equation where the coeficients are a = 1, b = -3 ...
Read More At : coolconversion.com...

Solving Quadratic Equations by Factoring | Purplemath


The new thing here is that the quadratic expression is part of an equation, and you're told to solve for the values of the ... when solving quadratic equations ...
Read More At : www.purplemath.com...

Suggested Questions And Answer :



Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

2/×+2+4/×-5=28/(×+2)(×-5)

If you mean 2/(x+4) + 4/(x-5) = 28/( (x+2)(x-5) ) then: Multiply both sides by (x+4)(x+2)(x-5) 2(x+2)(x-5) + 4(x+4)(x+2) = 28(x+4) x(x^2 - 3x - 10) + 4(x^2 + 6x + 8) = 28x + 112 x^3 - 3x^2 - 10x + 4x^2 + 24x + 32 = 28x + 112 x^3 + x^2 + 14x + 32 = 28x + 112 x^3 + x^2 - 14x - 80 = 0
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

Prove the quadratic equation

A quadratic equation in the standard form is given by ax 2 + bx + c = 0 where a, b and c are constants with a not equal to zero. ...Solve the above equation to find the quadratic fomulas Given ax 2 + bx + c = 0 Divide all terms by a x 2 + (b / a) x + c / a = 0 Subtract
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve for x when (.182+x)/(.106-2x)=3.24

solve for x when (.182+x)/(.106-2x)=3.24 Im trying to solve for x its for a chemistry equation but i need to solve for x using the quadratic equation and i dont know which equals a b and c to find x. ************************** You can't solve this with the quadratic formula, because there is no x^2
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

how to solve this quadratic equation x^2-2^x-13=0

I think you may have typed this in wrongly because the term 2^x is not a permitted term in a quadratic equation. As it stands the solution to the equation is about -3.6168. Let's say you made a mistake in typing and the middle term is 2*x or 2x, then the solution exists but it is irrational (i
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve for x in this quadratic equation: 4x^2 + 5x = 6

Yes, sometimes factoring doesn't work. That's when we fall back on the quadratic formula. 4x^2 + 5x - 6 = 0 This is in the general form, y = ax^2 + bx + c. From that, we extract the values we need when we use the quadratic formula.        -b ± sqrt(b^2 - 4ac) x = ----
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

3x + 6y – 6z = 9 2x – 5y + 4z = 6 -x +16y + 14z = -3 what is the answer

3x + 6y – 6z = 9 2x – 5y + 4z = 6 -x +16y + 14z = -3 what is the answer how do you solve it and what are the answers ? 1)  3x + 6y – 6z = 9 2)  2x – 5y + 4z = 6 3)  -x +16y + 14z = -3 The first objective is to eliminate z so we can solve for x and y. It's a multi-step proces
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

Find the orthogonal canonical reduction of the quadratic form −x^2 +y^2 +z^2 −6xy−6xz+2yz. Also, find its principal axes, rank and signature of the quadratic form.

4.4 Systems of Equations - Three Variables Objective: Solve systems of equations with three variables using addi- tion/elimination. Solving systems of equations with 3 variables is very simila r to how we solve sys- tems with two variables. When we had two variables we reduced
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

please help solve this quadartic problem step by step 26r-2=3rto the 2nd power also to simlify it in the end

26r-2=3r^2. The standard quadratic form is ax^2+bx+c=0, where x is the unknown and a, b and c are numbers. The unknown is r in this problem, so let's put the equation into quadratic form: 3r^2-26r+2=0. Note the sign changes as terms are transferred from one side to another, and also note that,
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve 14x-y=6 for y

14x-y=6 Since 14x does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 14x from both sides. -y=-14x+6 Multiply each term in the equation by -1. -y*-1=-14x*-1+6*-1 Multiply -y by -1 to get y. y=-14x*-1+6*-1 Simplify the right-hand side of the e
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

Solve the equation p^2+p(x+y)+xy=0

Question:  Solve the equation p^2+p(x+y)+xy=0. Its related to engineering math -  Clairaut's equation. Since Clairaut's equation is a differential equation, then I am assuming that p means the first differential, dy/dx, or y'. You equation actually then is: (y')^2 + (y')*(x+y) + xy =
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question

Notice: Undefined variable: position5 in /home/domains2/public_html/painphr.com/show.php on line 357
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.1078 seconds